COMPANY PERCEPTION ON THE EMPLOYABILITY SKILLS OF INDUSTRIAL TRAINING STUDENTS - Hassan, Siti Nor Habibah; Mohd Zamberi, Mahanum; Mohd Zamberi, Mahanum; Khalil, Siti Nurhaida; Sanusi, ï»¿Nortazi; Wasbari, Faizil; Kamarolzaman, Anita Akmar (Journal of Technical Education and Training, 2013)
Employability is the main concern for students and universities. It is one of the objectives of Ministry of Higher Education (MOHE) as to produce skilled, experienced and knowledgeable graduates to fulfil manpower needs with 75% of the graduates employed in their relevant fields within six months upon graduation. This study was conducted to review the company perception on the employability skills possess by Mechanical Engineering students in Universiti Teknikal Malaysia Melaka who has undergone their industrial training program in respective company. Five elements of employment skills studied here are based on the generic student attributes (GSA) established by MOHE i.e. communication skills, teamwork skills, critical thinking, work attitude and long life learning. It used to ensure the students will enrich themselves as a competent and comprehensive student after graduated. Questionnaire was prepared in three phases. Phase 1 and 2 are about the adaptability of students to their working environment and how the knowledge and experience in classroom being integrating into real life work experiences. Phase 3 is about the professionalism and work ethics among industrial training students. The result shows that most of the industrial supervisors agreed that industrial training program is one of the vital contributors to the employability skills.